LEGAL PROTECTION FOR WOMEN AND CHILDREN WHOSE MARRIAGES ARE NOT REGISTERED IN INDONESIA - Rochayat, Sukma; Khisni, Akhmad (Jurnal Hukum Khaira Ummah, 2023)
The benefits of marriage recording are very important. Marriage is not listed, greatly disadvantages the position of the married woman and the child being born. There is no legal consequence for undocumented marriages. Wife and child have no legal standing and no legal protection. There are sanctions for offenders of marriage registration law. If marriage has taken place, then it can be acknowledged to the child and performed marriage itsbat.Keywords : Legal Protection, Women and Children, Marriage